The financial implications of technology adoption on precision farming applied to conservation farming systems in the Overberg wheat producing area - Somtsewu, Lizalise (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.